Evaluation of Fondaparinux Use on Kidney Function in Hospitalized COVID-19 Patients with Decreased eGFR - Putri Nurhidayah, Eka; Didik Hasmono; Ruddy Hartono (Jurnal FARMASIMED (JFM), 2025)
Background: The COVID-19 pandemic has resulted in increased hospitalization rates among patients with multisystem complications, including coagulation disorders and decreased renal function. Fondaparinux, a synthetic anticoagulant with a lower risk of thrombocytopenia, is often used as an alternative to heparin. However, its use in patients with reduced glomerular filtration rate (eGFR) remains debatable, as its elimination is dependent on renal function. Objective: This study aims to evaluate the impact of fondaparinux on renal function, specifically examining changes in eGFR and serum creatinine levels in COVID-19 patients with impaired renal function during treatment at Bhayangkara South Surabaya Hospital. Methods: This research employed a retrospective observational quantitative approach, involving COVID-19 patients who received fondaparinux at the inpatient facility of Bhayangkara Hospital from June 2020 to October 2021. Data were collected from the medical records of patients during their hospitalization, including fondaparinux dosage and eGFR and serum creatinine values, as well as other relevant clinical parameters. Statistical analysis using the Wilcoxon test was conducted to assess significant differences in serum creatinine and eGFR values following fondaparinux administration. Results: Of the 535 patients analyzed, 56 medical records met the inclusion criteria. The results of the Wilcoxon test analysis showed that there was a significant increase in eGFR (p-value 0.012, CI 95%; p-value 0.043, CI 95%; p-value 0.000, CI 95%), a substantial decrease in SCr (p-value 0.035, CI 95%; p-value 0.043, CI 95%; p-value 0.000, CI 95%) based on each degree of COVID-19 severity. Conclusion: The use of fondaparinux may improve kidney function, as indicated by significant decrease in serum creatinine and an increase in eGFR. Furthermore, no bleeding incidents were observed during the use of fondaparinux.